KONSEP DIRI PRIA METROSEKSUAL DI KOTA PEKANBARU (DALAM PERSPEKTIF FENOMENOLOGI) - Perdana, Nada; Wirman, Welly (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Metrosexual men generally are in larger urban centers such as the city of Pekanbaru, with a neat appearance, good looking, smells good, charming and characteristic of its own. The phenomenon of the metrosexual man is a unique behavior in urban culture, they generally have a masculine image but is concerned about the appearance, body treatments, hanging out with their friends. Although, we know that is like like to concerned about the appearance and body treatments in generally are woman, that things cause positive stigma from society, from the stigma will form self-concept metrosexual man.This research aims to Known as metrosexual male self-concept cover physical, psychological, social and motives that influence self-concept formation metrosexual man in the city of Pekanbaru. This research uses qualitative research methods to conduct phenomenologhy approach. Subjects in this study amounted to 9 people. Data collection techniques are grouped through participant observation, in-depth interviews, and documentations. This study uses data validity checking technique through extended participation and triangulation.The results of this research are that self-concept metrosexual man in Pekanbaru has its own self-concept, with various aspects of the physical, psychic, and social. And also metrosexual Men in Pekanbaru city also has its own motive that cause their right to live the lifestyle as a metrosexual man, and they have a positive self-concept of self, good personality, visible from the appearance, as well as a positive attitude towards the environment.Keywords : Self Concept, Symbol Interaction, Metrosexual Male, Phenomenology.